Process of Internalizing Organizational Culture Among Millennial Employees - Iroth*, Yosie William; Jamalullail, Jamalullail (Riwayat: Educational Journal of History and Humanities, 2023)
The Covid-19 pandemic situation accelerates changes, shifts or causes changes that we feel. This research is qualitative research where qualitative research is based on the philosophy of phenomenology and the human approach and stands on the ability to understand, understand phenomena and interpret from researchers (2021). This research will focus on the phenomenon of the millennial generation where the Millennial generation has dominated the world labor market. The main background for this research is change in the world and work culture as well as shifts in the labor market as the main background. The researchers found from all sources from all sample companies that after the Pandemic, companies used a face-to-face approach to ensure direct interaction in organizational culture communication. The results of data collection and the results of in-depth interviews with informants found that the openness of the informants was also influenced by the atmosphere of the organization in which they worked. An increasingly open organizational communication culture that is tailored to employee profiles is the approach expected by employees, especially millennials.